Video feedback combined with peer role-playing: a method to improve the teaching effect of medical undergraduates - Jiwu Wang; Birong Wang; Dan Liu; Yiqun Zhou; Xin Xing; Xianggui Wang; Wei Gao (BMC Medical Education, 2024)
Abstract Objective The purpose of this study was to investigate the effectiveness of implementation of video feedback combined with peer role-playing (PRP) teaching method in medical undergraduates adopting problem-based learning (PBL) teaching mode. Methods The undergraduates of five-year clinical medicine who get enrollment of Wuhan local University from 2016 and 2018 were selected to be the research objects. The same grade level is randomly divided into several groups to carry out PBL, with 6–10 students in each group. Following the principle of voluntary participation, 34 students were enrolled in the study group and 33 students in the control group finally. The research regards group as the unit, and study report in group should be carried out to fulfill the research. In the study group, the students were asked to perform PRP report, and the report videos were used for feedback. At the same time, the control group reported by PPT, and the feedback was carried out according to the PPT. At the end of the study, the “Competency Improvement Satisfaction Questionnaire (CISQ)” was distributed to investigate students’ satisfaction with this teaching method to improve their ability, Arizona Clinical Interview Score (ACIR) was administered in Chinese by a trained teacher unrelated using PRP method to assess students’ clinical inquiry ability and communication skills, and theory test was performed to assess mastery of theoretical knowledge. Results The results show that the study group is superior to the control group in improving the interest of learning and the ability of independent learning, interpersonal communication and active problem solving. Although it is in terms of the confidence in becoming a real doctor and the ability of teamwork, language expression, clinical thinking cultivated, active knowledge acquired and understood that study group are better than the control group, the difference was not statistically significant. ACIR shows that the study group is significantly better than the control group in organization, timeline planning, and transition statements, openly questioning, smooth progress, and avoiding repetition, summarizing, understandable language, documentation and total score. There is no significant difference in eye contact and no interruption. The differences between the two groups are not statistically significant in terms of responsing to concerns, positive feedback, and additional questions. The theoretical test scores of the study group are significantly higher than those of the control group. Conclusion Video feedback combined with peer role-playing teaching method implemented in medical undergraduates adopting PBL teaching mode is effective, it could stimulate interest in learning actively, improve interpersonal communication ability, improve learning efficiency and clinical knowledge and skills, and improve the confidence of becoming a real doctor. It is worthy of further research and promotion.